Latent autoimmune diabetes in adults: a focus on β-cell protection and therapy - Yin, Wenfeng; Luo, Shuoming; Xiao, Zilin; Zhang, Ziwei; Liu, Bingwen; Zhou, Zhiguang (Frontiers in Endocrinology, 2022)
Latent autoimmune diabetes in adults (LADA) is a heterogeneous disease sharing some phenotypic, genetic, and immunological features with both type 1 and 2 diabetes. Patients with LADA have a relatively slow autoimmune process and more residual islet β-cell function at onset, allowing a time window to protect residual islet β cells and delay or inhibit disease progression. It is crucial to discover various heterogeneous factors affecting islet β-cell function for precise LADA therapy. In this review, we first describe the natural history of LADA. Thereafter, we summarize β-cell function-related heterogeneous factors in LADA, including the age of onset, body mass index, genetic background, and immune, lifestyle, and environmental factors. In parallel, we evaluate the impact of current hypoglycemic agents and immune intervention therapies for islet β-cell protection. Finally, we discuss the opportunities and challenges of LADA treatment from the perspective of islet β-cell function protection.